The dramaturgical setting in Viejas ilusiones by Eduardo Rovner - Vera Latorre, César Wilfredo (2022)
The article proposes an approach to Viejas ilusiones, work of the playwright Eduardo Rovner. It will seek to analyze the main dramaturgical tools and strategies applied in the text: how dramatic tension is generated, how humor operates, what criteria are applied in character profiling and, in general, how these and other mechanisms are combined in the play. The study concludes that the play builds dramatic tension through the simultaneous use of three levels of conflict. Also, that the age proposal of the characters constitutes a comic premise that opens a spectrum of games and perspectives that sustain humor, promote theatricality and stimulate the viewer’s awareness of artifice. Finally, it is suggested that one of Rovner’s contributions consists in having resemantized the genre of the European tragicomic farce to portray, in a humorous way, the manias and contradictions of Latin American society.